(untitled) (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Background: While rapid nurse response time is a critical performance indicator in Emergency Departments (ED) to ensure patient safety, perceived service quality is increasingly recognized as a multifactorial construct. Technical efficiency alone may not fully align with the qualitative expectations of patients. Objective: This study aims to analyze the relationship between nurses’ response time and patient care quality in the ED of Prof. Dr. Soekandar Regional General Hospital, Mojokerto Regency. Methods: An analytic observational study with a cross-sectional design was conducted. A sample of 144 respondents was selected via simple random sampling. Data were collected using observation sheets and a validated multidimensional service quality questionnaire (Cronbach’s alpha = 0.84), then analyzed using the Spearman Rank correlation test. Results: The majority of respondents (95.8%) experienced a fast response time (≤5 minutes), yet 61.1% perceived the service quality as only "Fairly Good". A statistically significant relationship was identified (p=0.046), although the correlation coefficient (r=0.166) indicated a very weak positive relationship. Conclusion: There is a statistically significant but very weak relationship between nurse response time and patient care quality. These findings suggest that technical speed is not the primary determinant of quality perceptions; instead, other multifactorial dimensions—such as empathy and therapeutic communication—likely play a more substantial role in shaping patient evaluations.